The role of radiotherapy for patients over age 60 with diffuse large B-cell lymphoma in the rituximab era. Issue 8 (2nd August 2016) - Cassidy, R. J.; Jegadeesh, N.; Switchenko, J.; Danish, H.; Esiashvili, N.; Flowers, C. R.; Khan, M. K.
Abstract: The role of consolidative radiotherapy (RT) in patients ≥60 years old with DLBCL in the rituximab era is controversial. We examined the impact on disease control and overall survival by the addition of consolidative RT after completion of chemotherapy, while adjusting for known adverse risk factors. Retrospective chart review from 2004 to 2012 of 83 consecutive patients ≥60 years old with DLBCL treated in the rituximab era, 68 of which had a complete response to chemotherapy, was performed. Amongst patients with a complete response, consolidative RT use was associated with 100% 5-year local control, improved progression-free survival ( p = 0.047), and a trend for overall survival ( p = .098) on multivariate analysis. Amongst all patients, the use of consolidative RT was associated with improved overall survival ( p = 0.03). The use of consolidative RT should be considered for patients ≥60 years old independent of stage and response to chemotherapy.